Complementary Approaches Towards a Universal Model of Glacier Surges - Terleth, Yoram; Van Pelt, Ward J. J.; Pohjola, Veijo A.; Pettersson, Rickard (Frontiers in Earth Science, 2021)
Although many convincing, diverse, and sometimes competing models of glacier surging have been proposed, the observed behavior of surging glaciers does not fit into distinct categories, and suggests the presence of a universal mechanism driving all surges. On the one hand, recent simulations of oscillatory flow behavior through the description of transient basal drag hint at a fundamental underlying process. On the other hand, the proposition of a unified model of oscillatory flow through the concept of enthalpy adopts a systems based view, in an attempt to rather unify different mechanisms through a single universal measure. While these two general approaches differ in perspective, they are not mutually exclusive, and seem likely to complement each other. A framework incorporating both approaches would see the mechanics of basal drag describing ice flow velocity and surge propagation as a function of forcing by conditions at the glacier bed, in turn modulated through the unified measure of enthalpy.